2013
DOI: 10.1177/0309364612470964
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of lower limbs of healthy Chinese people sitting cross-legged

Abstract: Such motion ranges were likely to result in prosthetic dislocation. The results would provide valuable references for prosthesis design in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
0
9
1
Order By: Relevance
“…There is the need to undertake more demanding activities and postures in this population. Sitting cross-legged or sitting on the floor are routine living activities that would constitute a common expectation in patients having their hips replaced in the Middle East ( 20 ). Additionally, the reported THR techniques reported in western populations do not account for the persistent cross-legged sitting position.…”
Section: Introductionmentioning
confidence: 99%
“…There is the need to undertake more demanding activities and postures in this population. Sitting cross-legged or sitting on the floor are routine living activities that would constitute a common expectation in patients having their hips replaced in the Middle East ( 20 ). Additionally, the reported THR techniques reported in western populations do not account for the persistent cross-legged sitting position.…”
Section: Introductionmentioning
confidence: 99%
“…Their average age was 71.7 years (range 58-82 years). The average number of levels fused was 7.5 segments (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). LL while standing improved significantly from 2.7° ± 20.9° before surgery to 32.9° ± 13.7° after surgery.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, this is insufficient for an accurate evaluation of the risk of THA dislocation for ASD patients with LSF. While studying 3D joint kinematics during activities of daily living (squatting, kneeling, and sitting cross-legged), the ranges of hip motion required to perform these activities in healthy subjects were revealed 11,12) . Nevertheless, the range of hip motion required in patients undergoing LSF remains unknown.…”
mentioning
confidence: 99%
“…16 The sitting cross-legged posture is a posture commonly found in Asian cultures where sedentary lifestyle is commonly, and the mechanical form shows the form of flexion, abduction and external rotation of the hip joint, ankle joints show plantar flexion and dorsi-flexion, and inversion and eversion in a rather little range. 17,18 For the average angle of the sitting cross-legged posture, Kapoor et al 17 reported 91° flexion, 39° abduction and external rotation 49° for the hip joint, the knee joint was flexion at 135°, and the ankle joint dorsiflexion was 23°. Also, Zhou et al 18 found that the hip flexion in the sagittal plane was 101.7°, the knee joint flexion was 131.9°, the ankle joint dorsi-flexion was 12.3°, and the plantar flexion was 20.2°.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 For the average angle of the sitting cross-legged posture, Kapoor et al 17 reported 91° flexion, 39° abduction and external rotation 49° for the hip joint, the knee joint was flexion at 135°, and the ankle joint dorsiflexion was 23°. Also, Zhou et al 18 found that the hip flexion in the sagittal plane was 101.7°, the knee joint flexion was 131.9°, the ankle joint dorsi-flexion was 12.3°, and the plantar flexion was 20.2°. In the movement of the frontal plane, the average abduction of the hip joint was 43.2°, inversion of the ankle joint was 22.8°, eversion was 12.3°, the external rotation of the hip joint was 36.4°, and the internal rotation of the knee joint was 32.4°.…”
Section: Introductionmentioning
confidence: 99%